Results of treatment of acute occlusions of limb arteries at a university hospital-retrospective study - Teodoro, Caroline [UNESP]; Bertanha, Matheus [UNESP]; Girard, Flavia Potsch Camara Mattos [UNESP]; Sobreira, Marcone Lima [UNESP]; Yoshida, Ricardo de Alvarenga [UNESP]; Moura, Regina [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2020)
Background: Acute arterial occlusions (AAO) in limbs have been increasing in parallel with population longevity. Objective: To assess risk factors, limb salvage rates, and survival of patients with AAO treated at a University Hospital. Methods: Retrospective cohort study of consecutive patients. Outcomes included: patency, symptoms, comorbidities, Rutherford category, arteries occluded, postoperative complications, and 30-day limb salvage and mortality rates. Results: Medical records were evaluated from 105 patients, predominantly males (65.7%), with ages ranging from 46 to 91 years. Etiology: thrombotic (54.3%), embolic (35.2%), and undefined (10.5%). About 2/3 of the patients were assessed as Rutherford category II or III. Associated symptoms: pain (97.1%), coldness (89.5%), pallor (64.7%), sensory loss (44.7%), paralysis (30.5%), anesthesia (21.9%), edema (21.9%), and cyanosis (15.2%). Associated comorbidities: hypertension (65.0%), smoking (59.0%), arrhythmias (26.6%), dyslipidemia (24.0%), and diabetes (23.8%). The distal superficial femoral-popliteal segment was the most affected (80%). Thromboembolectomy with a Fogarty catheter was performed in 73.3% of cases (81.0% of embolic cases, 71.9% of thrombotic cases, and 54.5% of cases with undefined etiology) and was the only treatment used in 41 cases (39.05%), among which there were 11 reocclusion, 20 amputations, and 14 deaths. Arterial reocclusion was more frequent in thrombosis cases (12.9%, p = 0.054). Within 30 days of treatment, total mortality was 14.6%, and 19.8% of cases underwent major amputation, which was less frequent among Rutherford Class I patients (p = 0.0179). Conclusion: Treatment of AAO was primarily performed by thromboembolectomy with a Fogarty catheter, either alone or in combination with other treatments, achieving amputation and complication rates compatible with the best results in the literature and were progressively lower in less advanced Rutherford categories.
Resultados do tratamento das oclusões arteriais agudas de membros em hospital universitário – estudo retrospectivo
Keywords: Balloon Embolectomy; Ischemia; Lower Extremity; Upper Extremity